Drawn on the way : A Guide to Capturing the Moment Through Live Sketching - Nisbett, Sarah (Quarry Books, 2021)
Drawn on the Way features techniques, tips, and projects for creating quick, lively sketches--portraits, figures, still life, scenes, nature, and more--that capture the beauty of a fleeting moment and connect us to the world.